Analisis Kualitas Anyaman Eceng Gondok Sebagai Penentu Kelulusan Produk Ekspor Pada Pengrajin di Desa Sukaraja - Nuralinda, Taliya (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
This research aims to analyze the quality of water hyacinth weaving as a determinant of product eligibility for export by artisans in Sukaraja Village, Rajapolah, Indonesia. Utilizing a qualitative descriptive method, this study focuses on exploring production techniques, quality assessment processes, and challenges faced by local artisans in meeting export standards. Data collection involved direct observation, in-depth interviews with artisans and exporters, and documentation of the weaving production stages. Results show that despite traditional manual tools and limited technological support, artisans exhibit strong creativity. However, the lack of standardization, inconsistent quality, and limited understanding of international requirements, especially from countries like Japan, hinder product acceptance in global markets. Improving quality control, design innovation, and market knowledge are essential for enhancing competitiveness.